Major Depressive Disorder (MDD): A Multifactorial Mental Health Crisis and Approaches to Holistic Management - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammed (Kwaghe International Journal of Sciences and Technology, 2025)
MDD, also known as Major Depressive Disorder, or clinical depression, is one of the most common and debilitating mental illnesses worldwide since it affects a person’s emotional, cognitive, and physiological functioning balance. Sufferers typically experience unrelenting low mood, anhedonia or lack of interest in activities, extreme tiredness, and numerous loopy mental and physical symptoms that negatively affect normal functioning. It’s worth emphasizing that a complex disorder, not solely an emotional state, depression arises as a result of the interplay of genetics, predisposition to the illness, neurobiological underpinnings, psychosocial and environmental stressors, as well as their myriad factors. This paper analyzes the causes, symptoms, diagnostic guidelines, and the most recent methods of treatment available for MDD. Special focus is given to psychotherapy, pharmacologic approaches, lifestyle changes, and the necessity for a holistic approach that integrates all dimensions of patient care.